Simulation-Based Study of Structural Changes in Electrical Time-Series Signals - Živković, Luka; Hederić, Željko; Benšić, Tin; Kurtović, Goran; Stojkov, Marinko (Journal of Energy Technology, 2025)
This paper addresses the detection of changes in electrical signals typical for industrial and power systems, using statistical indicators. A dedicated MATLAB algorithm was developed to identify change points by tracking shifts in signal behavior and statistical properties. To evaluate the method, synthetic signals were generated through simulation to reproduce common patterns observed in these systems, allowing testing under different operating conditions and varying noise levels. The results demonstrate that the algorithm reliably detects change points across multiple scenarios, showing both flexibility and robustness. This study highlights the value of simulation-based signal generation as a controlled environment for testing detection methods and provides a foundation for future application to more complex real-world electrical signal analysis tasks.